Leadership Education and Organizational Management of the Dewan Kerja Ranting (DKR) Tegalwaru, Purwakarta - Haqiqi, Abdillah; Fauzan N, Adam; Dewi, Ratna; Arobi, Thohal; Jasrudin, Akhmad; Ahmadi, Rizki; Ridwanullah, M.S. (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze leadership education management and organizational management at the Dewan Kerja Ranting (DKR) Tegalwaru, Purwakarta. The research focuses on the planning, implementation, and evaluation of leadership programs, as well as the organizational dynamics carried out by DKR as a forum for developing Scout Penegak and Pandega cadres at the branch level. This study uses a descriptive qualitative approach with data collection techniques including interviews, observations, and document studies. The analysis integrates concepts of educational management, organizational leadership, and empirical findings from previous research. The results indicate that leadership education management at DKR Tegalwaru has been implemented systematically through structured work programs, although challenges remain in terms of implementation consistency and cadre capacity building. This study is expected to serve as a reference for developing youth organization management based on leadership education.